Grandhalaya Samachara Sastra Avalokanam: Vyasasankalanam by Prof. A A N Raju (A Collection of Essays on Library and Information Science (Telugu) (Srirekha Publications, 2012, XII, 346p, Paperback, Price ` 300/-) - Tukaram, K. (Journal of Information and Knowledge, 2014)
No abstract